Indole-3-acetic acid induced cardiogenesis impairment in in-vivo zebrafish via oxidative stress and downregulation of cardiac morphogenic factors - Nayak, S.P. Ramya Ranjan; Boopathi, Seenivasan; Almutairi, Bader O.; Arokiyaraj, Selvaraj; Kathiravan, M.K.; Arockiaraj, Jesu (Environmental toxicology and pharmacology, 2024)
Plant growth regulators (PGRs) are increasingly used to promote sustainable agriculture, but their unregulated use raises concerns about potential environmental risks. Indole-3-acetic acid (IAA), a commonly used PGR, has been the subject of research on its developmental toxicity in the in-vivo zebrafish model. IAA exposure to zebrafish embryos caused oxidative stress, lipid peroxidation, and cellular apoptosis. The study also revealed that critical antioxidant genes including sod, cat, and bcl2 were downregulated, while pro-apoptotic genes such as bax and p53 were upregulated. IAA exposure also hampered normal cardiogenesis by downregulating myl7, amhc, and vmhc genes and potentially influencing zebrafish neurobehavior. The accumulation of IAA was confirmed by HPLC analysis of IAA-exposed zebrafish tissues. These findings underscore the need for further study on the potential ecological consequences of IAA use and the need for sustainable agricultural practices. [Display omitted] •Indole-3 acetic acid (IAA) induced embryotoxic and teratogenic effect in embryo.•IAA led to an increase in oxidative stress, lipid peroxidation and cellular apoptosis.•Down regulation in antioxidant and up regulation in pro-apoptotic genes due to IAA.•IAA exposure hindered cardiogenesis in developing embryos.•IAA is altering neurobehavior and tissue IAA accumulation in in-vivo larval model.